Unique inflammatory signature in haemophilic arthropathy: miRNA changes due to interaction between blood and fibroblast‐like synoviocytes. Issue 24 (7th November 2020) - Mignot, Sandra; Cagnard, Nicolas; Albaud, Benoit; Bally, Cécile; Siavellis, Justine; Hermine, Olivier; Frenzel, Laurent
Abstract: In haemophilia, the recurrence of hemarthrosis leads to irreversible arthropathy termed haemophilic arthropathy (HA). However, HA is a unique form of arthropathy in which resident cells, such as fibroblast‐like synoviocytes (FLS), come into direct contact with blood. Therefore, we hypothesized that FLS in HA could have a unique inflammatory signature as a consequence of their contact with blood. We demonstrated with ELISA and ELISPOT analyses that HA‐FLS expressed a unique profile of cytokine secretion, which differed from that of non‐HA‐FLS, mainly consisting of cytokines involved in innate immunity. We showed that unstable cytokine mRNAs were involved in this process, especially through miRNA complexes as confirmed by DICER silencing. A miRNOME analysis revealed that 30 miRNAs were expressed differently between HA and non‐HA‐FLS, with most miRNAs involved in inflammatory control pathways or described in certain inflammatory diseases, such as rheumatoid arthritis or lupus. Analysis of transcriptomic networks, impacted by these miRNAs, revealed that protein processes and inflammatory pathways were particularly targeted in LPS‐induced FLS, and in particular vascularization and osteoarticular modulation pathways in steady‐state FLS. Our study demonstrates that the presence of blood in contact with FLS may induce durable miRNA changes that likely participate in HA pathophysiology.